APPLICATION OF GLASS IONOMER CEMENT (GIC) FOR REPAIRING DENTAL PULP BY MEASURING EXPRESSION OF DENTIN MATRIX PROTEIN-1 : APLIKASI SEMEN IONOMER KACA UNTUK PERBAIKAN PULPA GIGI DENGAN MENGUKUR EKSPRESI DENTIN MATRIKS PROTEIN-1 - Endang Suprastiwi; Siti Mardewi Soerono Akbar; Narlan Sumawinata; Ellyza Herda (TALENTA, 2013)
Glass ionomer cement (GIC) has a potential to improve the pulp by inducing Dentin Matrix Protein-1 (DMP-1) release that can mineralize dentin. This study used three types of glass ionomer cements; Conventional GIC i.e. GC Fuji IX; resin-modified glass ionomer cement (RMGIC) i.e. GC Fuji II LC and Nano particle of RMGIC i.e. Ketacâ„¢ N100 3MEspe. The three materials were applied to the tooth pulp of Macaca nemestrina. Expression of DMP-1 extract-dental pulp of the subjects was investigated by using ELISA. This study was statistically analyzed by using Mann-Whitney test. The result showed that GICs has a potential to induce the expression of DMP-1 and there was no significant differences among the three groups of GIC to induce DMP-1(pâ‰¥ 0,05). In conclucion, all tested materials have a potential in dental pulp repair by expressing DMP-1.